Growing Old in Cities. Council Housing Estates in Trieste as Laboratories for New Perspectives in Urban Planning - Bricocoli, Massimo; Marchigiani, Elena (European Spatial Research and Policy, 2012)
Significant ageing processes are affecting many regions across Europe and are changing the social and spatial profile of cities. In Trieste, Italy, a joint initiative by the public Health Agency and the Social Housing Agency has developed a programme targeting conditions that allow people to age at home. The outcomes of the programme stress the need to redesign and reorganise the living environment as a way to oppose to the institutionalisation of older people in specialised nursing homes. Based on intensive field work, this contribution presents and discusses the original and innovative inputs that the case study is offering to the Italian and European debate.